Trophic Niche Dynamics and Diet Partitioning of King Crab Lithodes santolla in Chile's Sub-Antarctic Water - Andrade Diaz, Claudia Daniela Yanett; Rivera, Cristobal; Daza, Erik; Almonacid, Eduardo; Ovando, Fernanda; Morello Repetto, Flavia; Pardo, Luis Miguel (My University, 2022)
The southern king crab Lithodes santolla is one of the most economically important fishery species in the southern waters of the Atlantic and Pacific Oceans. A combination of stomach content and stable isotope analyses was used to reveal the potential dietary characteristics, isotopic niche, overlap among maturity stages and sexes, and trophic relationships of an L. santolla population in the Nassau Bay, Cape Horn region. Stable isotope analyses indicated that L. santolla assimilated energy from a basal carbon source, the giant kelp Macrocystis pyrifera, forming the trophic baseline of the benthic food web. Moreover, the trophic position of L. santolla varied among late juveniles and adults, suggesting that the southern king crab does undergo an ontogenetic diet shift. L. santolla exhibited intraspecific isotopic niche variation, reflecting niche differentiation which allows the species to partition resources. The trophic relationships of L. santolla with the associated fauna suggested some potential interactions for food resources/habitat use when they are limited. This study is the first attempt to characterize the trophic dynamics of the southern king crab in the Cape Horn area and, by generating more data, contributes to the conservation of the king crab population and the long-term management of local fisheries that rely on this resource.
Keywords: crustacea; trophic ecology; macrocystis pyrifera; isotopic niche; stable isotopes; stomach content; fisheries; omnivory